Determining the Location Scheme and Area of Logistics Centers to Optimize the Distribution of Disaster Cluster Areas in West Java - Nafia, Isya; Darwin, Darwin (Jurnal Media Infotama, 2024)
The West Java province, with an area of ​​35,377.76 km² and consisting of 27 districts/cities, frequently experiences earthquakes, floods, and volcanic eruptions. This study identifies five efficient logistics center points to reach all areas within the Golden Hour (3 hours) during disasters. Using Voronoi diagrams and the K-Means algorithm, each logistics center point has specific requirements for logistics packages, including minimum volume and warehouse area. This underscores the importance of technology in enhancing precise and efficient emergency responses in West Java.